Controle de dissociação molecular com ferramentas de dinâmica não linear - Almeida Junior, Allan Kardec de [UNESP] (2013)
The main objective of this work is to use the nonlinear dynamics theory in the control of the molecular dissociation through the introduction of dissipation in a literature well-known model that consists of an interatomic interaction potential and of a perturbation given by the interaction between the molecule dipole – electric field. This field may be from the photons, because the incidence of photons has already proved to be an effective tool in molecular dissociation. First of all, the study shows the possibility of the dissociation control without dissipation in very specific conditions. These conditions are generalized as the work makes the introduction of the dissipation, like the initial conditions, exposure time to the perturbation and possible values of the control parameters (constants in the motion equations), showing the benefits the dissipation can bring to the control and to the description of the molecular dissociation. The system is trapped in an attractor whose energy is enough to bring dissociation in case it is subjected to only the Morse potential interaction. This study also sweeps the parameters in order to show that the dissociation can also be controlled to a wide range of the values of the control parameters. This work makes a study based in the dissociation probability as a function of each control parameter so the results of this work can be compared with results of other works already known in the literature